2023
DOI: 10.1161/jaha.122.027832
|View full text |Cite
|
Sign up to set email alerts
|

Association of Objective and Self‐Reported Sleep Duration With All‐Cause and Cardiovascular Disease Mortality: A Community‐Based Study

Abstract: Background Previous studies found an association between self‐reported sleep duration and mortality. This study aimed to compare the effects of objective and self‐reported sleep duration on all‐cause and cardiovascular disease (CVD) mortality. Methods and Results A total of 2341 men and 2686 women (aged 63.9±11.1 years) were selected from the SHHS (Sleep Heart Health Study). Objective sleep duration was acquired using in‐home polysomnography records, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Higher risk of mortality by cardiometabolic causes was associated with both irregular sleep and short sleep duration in our study. These findings are consistent with experimental and epidemiological evidence linking sleep regularity and duration with cardiometabolic health [ 4 , 8 , 12 , 21 , 41–46 ]. Experimental evidence in humans indicates that cardiometabolic risk factors, including arterial blood pressure, inflammatory markers, and insulin sensitivity are altered with reduced sleep duration [ 41 ], and under experimental conditions that disrupt circadian rhythms [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Higher risk of mortality by cardiometabolic causes was associated with both irregular sleep and short sleep duration in our study. These findings are consistent with experimental and epidemiological evidence linking sleep regularity and duration with cardiometabolic health [ 4 , 8 , 12 , 21 , 41–46 ]. Experimental evidence in humans indicates that cardiometabolic risk factors, including arterial blood pressure, inflammatory markers, and insulin sensitivity are altered with reduced sleep duration [ 41 ], and under experimental conditions that disrupt circadian rhythms [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…Experimental evidence in humans indicates that cardiometabolic risk factors, including arterial blood pressure, inflammatory markers, and insulin sensitivity are altered with reduced sleep duration [ 41 ], and under experimental conditions that disrupt circadian rhythms [ 42 ]. Epidemiological studies show that the risks of cardiovascular events and mortality are higher in short sleepers [ 4 , 8 , 43 , 44 ] across both objective and subjective measures of sleep duration. For sleep regularity, epidemiological studies using actigraphy have linked more variable sleep timing and duration with incident fatal and non-fatal cardiovascular disease [ 45 ] and metabolic abnormalities [ 46 ], and SRI-measured sleep regularity with cardiometabolic risk factors [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses indicated that divergence from the recommended 7 to 8 hours (7–8 h/day) of sleep was linked to increased risks of cardiovascular events and mortality [ 7 , 8 ]. It has been supported by accumulating evidence that adherence to a healthy sleep pattern including an adequate sleep duration (7–8 h/day) is associated with lower risks of all-cause and cardiovascular mortality [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep duration is the most important biomarker of sleep quantity and has effects on various systems . Short sleep duration was reported to be associated with multiple cardiovascular and endocrine diseases as well as all-cause mortality in the general population . In recent years, short sleep duration in people with OSA was found to be associated with insulin resistance, visceral obesity, and hypertension .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Short sleep duration was reported to be associated with multiple cardiovascular and endocrine diseases [16][17][18][19] as well as all-cause mortality in the general population. [20][21][22] In recent years, short sleep duration in people with OSA was found to be associated with insulin resistance, visceral obesity, and hypertension. [23][24][25] Nevertheless, the association between sleep duration and all-cause mortality in OSA was rarely investigated.…”
Section: Introductionmentioning
confidence: 99%